ICT Integration in Teaching English to Young Learners in Remote Settings: A Teacher’s Narrative Inquiry - Robiatul Adawiyah; Durratul Hikmah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explore the lived experiences of an English as a Foreign Language (EFL) teacher in integrating Information and Communication Technology (ICT) into English language teaching for primary school pupils in a remote area. This study employs a qualitative approach using a narrative inquiry design. The participant was an EFL teacher using the pseudonym, “Reyhan”. Data were collected through semi-structured interviews, classroom observations, and documentation, and analysed based on the dimensions of temporality, sociality, and place. The findings indicate that ICT integration is a dynamic and contextual process that develops through teaching experience, reflection, self-directed learning, professional collaboration, and adaptation to the learning context. Reyhan utilised various digital platforms and media aligned with learning objectives and pupils' characteristics to create more interactive, meaningful, and pupil-centred learning. The challenges included limited digital skills, unreliable internet access, limited technological facilities, and diverse pupils' characteristics. To address these challenges, Reyhan adopted adaptive strategies through self-directed learning, technological exploration, trial and error, collaboration with colleagues, peer tutoring, and alternative learning methods during technical difficulties. This study concludes that successful ICT integration depends on teachers' ability to continuously learn, adapt, reflect, and make pedagogical decisions appropriate to the learning context.